2009
DOI: 10.1037/a0016391
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys (Macaca mulatta) hear rising frequency sounds as looming.

Abstract: Rising sound intensity provides an important cue for the detection of looming objects. Studies with humans indirectly suggest that rising pitch can also signal a looming object. This link between rising intensity and rising frequency is puzzling because no physical rise in frequency occurs when a sound source approaches. Putative explanations include (a) the idea that the loudness of sound depends on its frequency, (b) the frequent co-occurrence of rising intensity with rising frequency in vocalizations genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…In the absence of clear changes in spiking under multisensory conditions, a neuron was said to not integrate its different inputs. However, more recent work, which has focused not only on spiking but also on changes in the local field potential (LFP - a measure of summed synaptic activity), has illustrated the presence of multisensory interactions in the LFP response in the absence of clear changes in neuronal spiking (Ghazanfar and Maier, 2009,Ghazanfar, et al, 2005,Ghose and Wallace, 2014,Kayser, et al, 2009,Sarko, et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In the absence of clear changes in spiking under multisensory conditions, a neuron was said to not integrate its different inputs. However, more recent work, which has focused not only on spiking but also on changes in the local field potential (LFP - a measure of summed synaptic activity), has illustrated the presence of multisensory interactions in the LFP response in the absence of clear changes in neuronal spiking (Ghazanfar and Maier, 2009,Ghazanfar, et al, 2005,Ghose and Wallace, 2014,Kayser, et al, 2009,Sarko, et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For example, Maier et al, (2004) showed that rhesus macaques associated complex tones that rose in intensity with expanding circles, which were thought to be perceived as aversive 'looming' or approaching stimuli by the macaques. Furthermore, macaques also associated rising frequency tones with expanding circles (Ghazanfar and Maier, 2009). A related effect known as the 'doppler illusion' is observed in humans: listeners report an increase in the pitch of a sound source moving towards them even though there is no change in the actual frequency of the sound (Neuhoff and McBeath, 1996).…”
Section: Structural Correspondencesmentioning
confidence: 99%
“…A related effect known as the 'doppler illusion' is observed in humans: listeners report an increase in the pitch of a sound source moving towards them even though there is no change in the actual frequency of the sound (Neuhoff and McBeath, 1996). However, although the macaques did not have any prior experience with the stimuli used in either study (Ghazanfar and Maier, 2009;Maier et al, 2004), it was not possible to establish whether the association between rising intensity and frequency with increasing size in multisensory looming signals is innately present, or dependent on experience. Therefore, the extent to which intensity-based associations represent fixed structural correspondences remains to be established.…”
Section: Structural Correspondencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Para alcanzar este fin, los resultados de los estudios en humanos adultos y recién nacidos son contrastados regularmente con información obtenida del trabajo con roedores, aves y monos. Los aspectos respecto a los cuales se realizan comparaciones abarcan la discriminación de fonemas, sílabas, palabras y oraciones, el aprendizaje de patrones gramaticales simples y de palabras, el rastreo de re gularidades distributivas de elementos (probabilidades transicionales y frecuencia de ocurrencia conjunta) y la extracción y generalización de reglas algebraicas en la señal del habla (entre otros: Brainard & Doupe, 2002;Elgier & Bentosela, 2009;Endress, Cahill, Block, Watumull & Hauser, 2009;Ghazanfar & Maier, 2009;Jakovcevic & Bentosela, 2012;Murphy, Mondragón & Murphy, 2008;Newport, Hauser, Spaepen & Aslin, 2004;Ohms, Escudero, Lammers & ten Cate, 2012;Pilley & Reid, 2011;Reed et al, 2003;Saffran et al, 2008;Sinnott & Gilmore, 2004;Toro & Trobalon, 2005; para una revisión general ver Barón, 2014 (Ramus, 1999). Tradicionalmente se han considerado tres tipos de isocronía (Gervain & Mehler, 2010;Toledo, 2009):…”
Section: Composición Del Lenguaje Y Estudio Psicolin-güístico Comparadounclassified